Analysis Water Pump Control System Using PID Based on PLC and HMI - Rachmawati, Angraini; Marindani, Elang Derdian; Sanjaya, Bomo Wibowo (Faculty of Engineering, Universitas Tanjungpura, 2025)
The liquid